Saturday

December 27, 2014

December 27, 2014

Posted by **Kendra** on Monday, October 29, 2012 at 3:37pm.

e^(2x+3) -7=0

ln(5-2x)=-3

- Calculus -
**Steve**, Monday, October 29, 2012 at 3:39pme^(2x+3) = 7

2x+3 = ln7

x = (ln7 - 3)/2

ln(5-2x) = 3

5-2x = e^3

x = (5 - e^3)/2

**Answer this Question**

**Related Questions**

Calculus - How do you us implicit differentiation to solve x( y + 2 )^5 = 8 x( y...

Pre calculus - How do I solve this exponent problem? I understand the exponent ...

math-calculus - solve 3|x-8|=2x+7 i not get how to solve this the 3 infront of ...

calculus - I am suposed to apply L'Hospitals rule to solve. I can't seem to ...

Calculus - solve for dv/du dQ/du= 38u + [(u+v)^2(18+19dv/du) -(2(18u+19v)(u+v)(1...

Calculus - I was able to solve (e), this is the only one I don't get. Determine ...

COLLEGE CALCULUS. HELP! - the fundamental theorem of calculus, f(x)=∫(0,x...

Calculus - Solve: dy = [2+(y-2x+3)^0.5]dx The answer in the book is 4(y - 2x + 3...

Calculus - Right now my class is working on exponential growth and decay. I know...

Calculus - Simplify. State the nonpermissible values. 4a^2-1/4a^2-16*2-a/2a-1 ...